Cultural Representation in The Distinctiveness of Madurese Language Poetry Di' Dhindi' Pocang as Cultural Preservation - Awik Tamara; Eti Setiawati (English Department FBS UNP, 2021)
The purpose of this study is to identify aspects of language peculiarities in the poem Di' Dhindi' Pocang then explore its cultural values as an effort to preserve culture. The method used was descriptive qualitative with a theoretical approach in the form of anthropolinguistic studies. Data collection techniques were carried out by interviewing, inventorying, transliterating, transcribing, and translating assisted by informants, as well as data classification. Data analysis was carried out by collecting data, then continued with data reduction, data presentation and conclusions. The results of this study are the language peculiarities in the SDP which include alliteration, assonance, substance, metaphor and meaningless words, as well as the cultural values represented in the SDP include, customs and harmony, togetherness and equality, divinity, and relationships with nature. The cultural values contained in SDP are important to understand. This understanding is intended to preserve and maintain culture. Efforts to preserve SDP can be carried out with culture experience in the form of direct involvement as ritual participants and culture knowledge, carried out by exploring culture in SDP, which is then documented and recorded in various forms, such as books, articles or scientific journals, tourist spots and others.